2019
DOI: 10.1017/s0022029919000414
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of casein genes

Abstract: This research paper addresses the hypothesis that comparative genomics can give a new insight into the functionality of casein genes with respect to the casein micelle. Comparative genomics is a rapidly emerging field in computational biology whereby two or more genomes are compared in order to obtain a global view on genomes as well as assigning previously unknown functions for genes. Casein genes are among the most rapidly evolving mammalian genes, with the gene products mainly grouped into four types (αs1-,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In reference to the aligned sequence of the CSN gene, high variation has been reported in all the CSN genes. Even though closely related species represent increased sequence similarity with conserved and non-conserved genomic regions (Madende and Osthoff, 2019). In the present study, sequence analysis of CN protein revealed 10 conserved motifs in buffalo, and cattle using the MEME tool.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In reference to the aligned sequence of the CSN gene, high variation has been reported in all the CSN genes. Even though closely related species represent increased sequence similarity with conserved and non-conserved genomic regions (Madende and Osthoff, 2019). In the present study, sequence analysis of CN protein revealed 10 conserved motifs in buffalo, and cattle using the MEME tool.…”
Section: Discussionmentioning
confidence: 57%
“…Caseins (αs1, αs2, β, and κ) are the primary components of milk protein content in dairy animals. All the mammalian CSN genes are rapidly evolving genes and are mainly classified into four types including CSN1S1, CSN2, CSN1S2, and CSN3 (Madende and Osthoff, 2019). The results of our molecular phylogenetic analysis of the CSN gene family are in consensus as all the representative species were clustered into four taxa.…”
Section: Discussionmentioning
confidence: 73%
“…In goats and cattle, these genes are mapped on chromosome 6 and span about 250 kb [6]. These genes have been characterized at the genomic [7], transcriptomic [8], and proteomic [9] levels. Furthermore, genetic polymorphisms and variants in casein genes have been reported in various animal species [10], including cattle [11][12][13], goats [14], and sheep [15], with goats and cows having the largest genetic variability.…”
Section: Introductionmentioning
confidence: 99%
“…Divergence in casein genes and the presence or absence of one or more genes encoding caseins explain the different biological and chemical functions of the casein micelles ( 45 ). The genes encoding α-caseins are absent in most mammalian species; for example, human milk lacks αs2-casein, and it may be possible that its role in casein micelle formation could be shifted to αs1-casein ( 14 ). In contrast, genes encoding β-and κ-caseins are widely distributed among mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative genomic analysis can provide new insights into the functionality of casein genes with respect to the caseins. Comparative genomic analysis is a rapidly emerging field in computational biology whereby two or more genomes are compared to obtain a global view of genomes and their deduced proteomes and assign previously unknown functions to genes with respect to their proteins (14). Computational chemical properties can also pave the way to predicting the properties of deduced proteins.…”
Section: Introductionmentioning
confidence: 99%